Caffeine improves sprint-distance performance among Division II collegiate swimmers - Vanata, D. F.; Mazzino, N.; Bergosh, R.; Graham, P. (The Sport Journal, 2014)
Caffeine has been identified as a possible ergogenic aid for athletic performance. The objective of this study was to evaluate the effects of caffeine on sprint-distance swim trials. Caffeine dosages of 3 milligrams per kilogram (mg.kg-1) of body weight and placebos were administered via vegan capsules to 30 Division II collegiate swimmers, (60.0% males, n=18), in a single blind, crossover study design. Capsules were administered 30-minutes prior to completing a 50-yard time trial using electronic touch-pads. Urine samples were collected and analyzed via High Pressure Liquid Chromatography (HPLC) to determine the amount of caffeine excreted in the urine. Significant improvements were observed between caffeine and placebo time trials, M=27.27 seconds, SD=3.65 vs. M=27.51 seconds, SD=3.74, t(29)=2.81, p=.009, respectively. Overall, 70.0% of all swimmers improved 50-yard swim times (n=21), with 61.1% (n=11) of males improving and 83.3% (n=10) of females. There was a significant difference between urinary caffeine levels after ingesting the placebo vs. the caffeine capsules, M=.733 micrograms per milliliter (mg.ml-1), SD=1.29 vs. M=2.69 mg.ml-1, SD=2.02, t(29)= -5.34, p<.001, respectively. Following supplementation, female swimmers excreted significantly more urinary caffeine than males, M=3.59 mg.ml-1, SD=2.23 vs. M=2.09 mg.ml-1, SD=1.68, t(28)= -2.11, p=.044, respectively. Overall, caffeine supplementation was found to significantly improve time trials of trained colligate swimmers. Additional studies are needed to identify factors associated with the variation of urinary caffeine excretion values observed between female and male athletes.